CME credit systems in three developing countries: China, India and Indonesia. Issue 1 (1st January 2015) - Miller, Lewis A.; Chen, Xuejun; Srivastava, Vaibhav; Sullivan, Lisa; Yang, Weiguang; Yii, Charity
Abstract : Introduction. Two of the largest countries in the world, still developing nations, China and Indonesia, have now created national credit systems for continuing medical education (CME). A third, India, has tried but succeeded only on a state-by-state basis. This study tracks the development of CME/continuing professional development (CPD) credit systems in these three major Asian countries, analyses the related administrative backgrounds and points to strengths and weaknesses of each system in terms of serving the goals of CME/CPD in impacting medical care systems. Methods. The authors researched national- and state-level government records to identify legal and regulatory data affecting CME in China, India and Indonesia. Information on current and future activities was gained from media reports. Results. In all three countries, CME/CPD systems evaluate physician continuing competence by counting credits or credit hours. Central health authorities in China and Indonesia have established national systems applying to all health professionals. In Indonesia, CME/CPD is mandatory for re-licensure; in China, it is necessary for career advancement and re-registration. An effort to develop mandatory CME requirements in India, for physicians only, failed because the central agency underwent a major overhaul. Nevertheless, 9 of 28 states in India have developed systems, all tied to re-registration. Discussion. A comparison of systems in the three countries shows that little attention has been paid to physician performance improvement or improved patient health outcomes. Needs assessments and outcomes measures are not regularly carried out. We did not find any evidence of programmes to train administrators or faculty in CME/CPD principles, with the possible exception of Indonesia. Suggestions are offered to CME system leaders and providers to help their counterparts in developing nations.